Greetings from the SERTOT President - Vaienti, Enrico (Acta Biomedica Atenei Parmensis, 2020)
Dear Members,we are going through a difficult period in every aspect, which has seen us to react to the epidemic aggression and then to reconstruct what has been damaged or destroyed. In the phase of overcoming the period of “heroic” activity, the risk is that there will be a tendency to tiredness and renunciation. We have to react and regain our personal and professional strength and even the SERTOT must react.Because of this, it is with great pleasure that I introduce the volume 4-2020 Acta Biomedica Supplement - Advances in Orthopaedics, Traumatology and Rehabilitation - SERTOT.The vitality of our Scientific Society is demonstrated by its ability to publish scientific papers also in this particular period of the life. This is the first issue in 2020 but I am confident that our Society will publish also to the second one. SERTOT has always stimulated their members to send articles to the magazine focused on different orthopaedics and traumatologic topics. For these reasons, I am very happy that, also in this circumstance, contributions have arrived particularly numerous.A special thanks to the Deputy Editors Francesco Pogliacomi and Paolo Di Benedetto for the personal commitment and passion dedicated to the magazine and to the sponsors who have guaranteed the release of this journal in the past years and this year.Sincerely